Stent as a bridge to surgery for malignant colonic obstruction: a retrospective study on survival and outcomes - Thanawin Wong; Tanawat Pattarapuntakul; Nisa Netinatsunton; Jaksin Sottisuporn; Thanapon Yaowmaneerat; Wongsakorn Chaochankit; Siriboon Attasaranya; Pimsiri Sripongpun; Naichaya Chamroonkul; Viraksakdi Chongsuvivatwong (BMC Gastroenterology)
Background In cases of malignant colonic obstruction (MCO), self-expandable metallic stents (SEMS) are used as a bridge to surgery, offering an alternative to emergency surgery. However, the long-term oncologic outcomes remain debated, particularly in developing countries where the cost of SEMS is a concern. This study aimed to evaluate overall survival (OS) and outcomes associated with SEMS as a bridge to surgery (SBTS) compared to direct emergency surgery (ES) in patients with acute MCO. Methods A retrospective study was conducted, including patients with potentially curable obstructed colon cancer who were treated with either SBTS or ES at a university hospital in Thailand from 2015 to 2022. We compared OS, 5-year OS rate, disease-free survival (DFS), postoperative morbidity, and complications between the SBTS and the ES groups. Results A total of 106 patients were eligible, 29 underwent SBTS, and 77 underwent ES. Baseline characteristics were similar except for ASA classification and chemotherapy rates. The median OS was 56.1 months, with no significant differences in OS (51.4 vs. 61.0 months, p = 0.67) or 5-year DFS (53.8% vs. 59.9%, p = 0.32) between the two groups. The SBTS group had higher rates of minimally invasive surgery (MIS) (65.5% vs. 16.9%, p < 0.001) and shorter postoperative stays (POS) (7 vs. 9 days, p = 0.026). Stage IV cancer and low serum albumin were poor prognostic factors for OS. Conclusion SEMS placement as a bridge to surgery had no significant impact on OS compared to ES, but it was associated with shorter hospital stays and higher rates of MIS.